Critical infrastructures : risk and vulnerability assessment in transportation of dangerous goods : transportation by road and rail /: risk and vulnerability assessment in transportation of dangerous goods : transportation by road and rail. (2016) - Vamanu, Bogdan I; Gheorghe, Adrian V; Katina, Polinpapilinho F
No abstract available